The impact of single windows on trade - Inmaculada Martínez-Zarzoso; Santiago Chelala (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2020)
This article is the first that quantifies the impact of single windows (SWs) on international trade globally. SWs function as a single point of entry and exit of the goods traded internationally and are therefore intended to facilitate trade. Using a structural gravity model for a panel of 176 countries from 1995 to 2017, we apply a log-log and a Poisson pseudo-maximum likelihood estimator (PPML) will multi-dimensional fixed effects to evaluate the extent to which export and import flows vary depending on whether or not countries have operational SWs. The main results from the linearized gravity model suggest that total trade between two countries with functioning SWs increases by about 37 percent, of which 23 corresponds to exports and 14 to imports. The result from the PPML estimation also indicate a positive and significant effect, which is however much smaller in magnitude.
Keywords: F13; O33; 330; International trade; single window; technology